Screening of depression among school-going adolescents of district Rawalpindi using PHQ-9 questionnaire, a cross-sectional study - Humaira Mahmood; Farooq, Waqas; Naheed Kazmi; Zainab Sabir; Izzah Nawaz; Khursand Bint-e-Azam (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the prevalence of depression and sociodemographic factors associated with depressive symptoms among adolescents. Method: The descriptive, cross-sectional study was conducted from July to November 2024 at public and private schools in Rawalpindi, Pakistan, ZA Public Secondary School, Government Graduate College Dhoke khabba, FG Sir Syed Model Public School (Boys), and Zia-ul-Islam National secondary school, and comprised students of either gender aged 14-17 years. The Patient Health Questionnaire-9 was used to screen and classify the severity of depressive symptoms. The association of demographic variables with depression severity was explored. Data was analysed using SPSS 27.0.1. Results: Of the 358 adolescents, comprising 190(53.1%) were boys, 168(46.9%) were girls and 116(38%) were aged 16 years. The level of depressive symptoms was minimal in 169(47.2%) cases, mild in 98(27.4%), moderate in 66(18.4%), moderately severe in 22(6.1%) and severe in 3(0.8%). Depression severity was significantly correlated with age, female gender and family income (p<0.05). Parental marital status and a history of mental illness in the parents did not significantly correlate (p>0.05) with severity of depressive symptoms. Conclusion: Depression was found to be highly prevalent among school-going adolescents, with more than half reporting mild to severe symptoms. Age and family income were the significant factors associated with depressive symptoms. Key Words: Adolescents, Depression, Depressive disorder, Mental health, PHQ9.